STRATEGIES ENHANCING PROFESSIONAL LEARNING COMMUNITIES OF SCHOOLS UNDER SURIN PROVINCE PRIMARY EDUCATIONAL SERVICE AREA OFFICE 3 - Saengtatton, Siriporn; Khamdit, Sinthawa (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2024)
The research aimed to 1) to study the current conditions, desirable conditions, and the needs of quality of enhancing Professional Learning Communities of schools under Surin Province Primary Educational Service Area Office 3 and 2) to develop strategies enhancing Professional Learning Communities of schools under Surin Province Primary Educational Service Area Office 3. The sample group were 101 school principals and 240 teachers, totaling 341 people. The informants were school administrators and heads of academic affairs teachers total 6 people finding by purposive sampling. Moreover, there were 5 experts who assessed the suitability and feasibility of the strategies finding by purposive sampling. Research instruments were 1) questionnaire: Reliability current condition is 0.977 and Reliability desirable conditions is 0.961.2) semi-structured interview and 3) appropriateness and feasibility assessment of the strategies. The frequency, percentage, means, standard deviation, Pearson product-moment correlation, Cronbach's alpha coefficient and Modified Priority Needs Index (PNImodified) were employed to analyze data. The findings of this research were as follows: 1) The overall current condition of enhancing Professional Learning Communities of schools was in the high level. Moreover, the desirable conditions of enhancing Professional Learning Communities of schools were in the highest level. Additionally, the priority of needs on enhancing Professional Learning Communities of schools was sorted in descending order including learning and professional development, collaborative team, kalayanamit community (true-friendship community), co-leadership community, community-supportive structure, and shared vision. 2) Strategies enhancing Professional Learning Communities of schools under Surin Province Primary Educational Service Area Office 3 consisted of 7 strategies for the shared vision, 8 strategies for the co-leadership, 8 strategies for the community-supportive structure, 10 strategies for the collaborative team, 7 strategies for the kalayanamit community (true-friendship community) and 7 strategies for the learning and professional development, totally 6 aspects 47 strategies. The result’s assessment of suitability and feasibility of strategies enhancing Professional Learning Communities of schools under Surin Province Primary Educational Service Area Office 3 indicated that suitability and feasibility in the highest level.